THE INFLUENCE OF LEARNING STYLE ON ACHIEVEMENT THROUGH MOTIVATION AS A MODERATOR VARIABLE - Istiningtiyas, Dwi (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2021)
The aim of the research is to describe and analyse: (1) to know how the students’ motivation, learning style and achievement are. (2) To know how far (a) the influence of motivation on achievement, (b) the influence of learning style on achievement, and (c) the influence of learning style on motivation. And (3) to find out whether there is any significance influence of learning style on achievement through motivation as a moderator variable. This research used quantitative approach as the research design. This research used 113 students as samples, who are selected randomly from a population of 334 seventh grade student of UPTD SMPN 02 Ngadiluwih Kediri. Meanwhile, the instrument used to collect data is a questionnaire. The result showed that: (1) the achievement is a low category, the motivation is a high category and the learning style is a low category. (2) (a) there is a significance influence of motivation on achievement. (b) There is a significance influence of learning style on their achievement. And (c) there is a significance influence of learning style on motivation. (3) There is not significance influence of learning style on their students’ achievement through motivation as a moderator variable.